Bibliometrix applied to computational simulation for wind generator - Viana, Tainan; Sales Costa, Alexandre; Albuquerque Fortes, Lara; Freitas de Andrade, Carla; Olímpio Moura Carneiro, Francisco; Moura de Oliveira, Mona Lisa (Latin American Journal of Energy Research, 2024)
This study presents a comprehensive bibliometric analysis of computational simulations in wind turbine projects, addressing their pivotal role amid growing demands for renewable energy and engineering project optimization. The primary objective is to discern trends, focal areas, and global collaboration networks.Utilizing Scopus and Web of Science databases, supported by CAPES, all pertinent publications on computational simulations in wind turbine projects were scrutinized. Bibliometric metrics were analyzed using the bibliometrix library in R.Findings reveal a increase in publications since 2022, particularly in aerodynamic optimization and offshore projects. Leading contributors are universities, research centers across Europe, North America, and prominently China. Co-authorship networks underscore significant collaborations among global academic institutions. Key terms such as "computational modeling," "CFD (Computational Fluid Dynamics)," and "wind turbine" predominate in literature.The analysis confirms the escalating significance of computational simulations in wind turbine projects, underscored by burgeoning publications and international partnerships. Integration of emerging technologies like artificial intelligence and machine learning into market practices is evident. This study serves as a foundational resource for future researchers and industry stakeholders, identifying promising avenues and areas necessitating further exploration.
Keywords: bibliometry; wind turbine; numerical study; aerodynamic optimization; renewable energy